Pengaruh Faktor Auditor terhadap Kualitas Audit di Perusahaan Properti dan Real Estate - Valencia Novelita; Nella Yantiana; Haryono, Haryono (Goodwood Akuntansi dan Auditing Reviu, 2025)
Purpose: This study aims to examine the influence of audit fee, audit tenure, time budget pressure, and public accounting firm (PAF) reputation on audit quality in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Methodology/approach: The study uses a quantitative approach with multiple linear regression analysis. Data were collected from annual financial reports of 22 companies over three years, resulting in 66 observations. Data analysis was conducted using SPSS 26 software, and classical assumption tests were performed, including normality, multicollinearity, heteroscedasticity (with robust regression), and autocorrelation tests. Results/findings: The results show that audit fee (p = 0.022) and PAF reputation (p = 0.000) have a significant negative effect on audit quality, while time budget pressure (p = 0.000) has a significant positive effect. Audit tenure (p = 0.869) does not significantly affect audit quality. The model explains 77.4% of the variance in audit quality (Adj R² = 0.774). Conclusion: External auditor factors significantly influence audit quality. Higher audit fees and strong PAF reputation may decrease independence, while appropriate time budget pressure enhances quality. This study contributes to strengthening agency theory and providing practical recommendations for regulators and auditors. Limitations: The study is limited to one industry sector and only includes four independent variables, which may not fully capture all factors affecting audit quality. Contribution: This study contributes to the auditing literature by highlighting how external factors influence audit quality. It provides insights for auditors, regulators, and corporate management in improving audit practices and maintaining professional independence in financial reporting.